Removal of Textile Dyes from Aqueous Solution by Heterogeneous Photo-Fenton Reaction Using Modified PAN Nanofiber Fe Complex as Catalyst - Xueting Zhao; Yongchun Dong; Bowen Cheng; Weimin Kang (International Journal of Photoenergy)
The modified PAN nanofiber Fe complex was prepared by the amidoximation and Fe coordination of PAN nanofiber was obtained using electrospinning technique and then used for the heterogeneous Fenton degradation of textile dyes as a novel catalyst. Some main factors affecting dye degradation such as Fe content of catalyst, irradiation intensity, H2O2 initial concentration, the solution pH as well as dye structure, and initial concentration were investigated. UV-Vis spectrum analysis and TOC measurement were also used to evaluate the dye degradation process. The results indicated that the modified PAN nanofiber Fe complex exhibited a much better catalytic activity for the heterogeneous Fenton degradation of textile dyes than the Fe complex prepared with conventional PAN yarns in the dark or under light irradiation. Increasing Fe content of catalyst or irradiation intensity would accelerate the dye degradation. And the highest degradation efficiency was obtained with 3.0 mmol L−1 H2O2 at pH 6. Moreover, this complex was proved to be a universal and efficient catalyst for degradation of three classes of textile dyes including azo dye, anthraquinone dye, and triphenylmethane dye. Additionally, the dye mineralization was also significantly enhanced in the presence of this complex.